Measurement of Protein Mobility in Listeria monocytogenes Reveals a Unique Tolerance to Osmotic Stress and Temperature Dependence of Diffusion - Tran, Buu Minh; Prabha, Haritha; Iyer, Aditya; O’Byrne, Conor; Abee, Tjakko; Poolman, Bert (Frontiers in Microbiology, 2021)
Protein mobility in the cytoplasm is essential for cellular functions, and slow diffusion may limit the rates of biochemical reactions in the living cell. Here, we determined the apparent lateral diffusion coefficient (DL) of GFP in Listeria monocytogenes as a function of osmotic stress, temperature, and media composition. We find that DL is much less affected by hyperosmotic stress in L. monocytogenes than under similar conditions in Lactococcus lactis and Escherichia coli. We find a temperature optimum for protein diffusion in L. monocytogenes at 30°C, which deviates from predicted trends from the generalized Stokes-Einstein equation under dilute conditions and suggests that the structure of the cytoplasm and macromolecular crowding vary as a function of temperature. The turgor pressure of L. monocytogenes is comparable to other Gram-positive bacteria like Bacillus subtilis and L. lactis but higher in a knockout strain lacking the stress-inducible sigma factor SigB. We discuss these findings in the context of how L. monocytogenes survives during environmental transmission and during interaction with the human host.